before you even start, did you notice the two equations have the same slope, but have different y-intercepts.
Thus they will never meet, and therefore there can't be a solution.
If you try it anyway ....
first equation:
y = 2x+3
sub in the second
2x-2 = 2x + 3
-2= 3 , mmmhhh, that's a good one!
If silly stuff like happens, then usually you can say , "there is no solution".
But you should still understand why that happens.
How would you solve y=2x+3 and y=2x-2 using the substitution.
2 answers
I understand. What would be the independent variable and dependent variable? Could you give me a real world situation to explain it.